A Naso-Orbito-Ethmoid (NOE) Fracture Associated with Bilateral Anterior and Posterior Frontal Sinus Wall Fractures Caused by a Horse Kick—Case Report and Short Literature Review - Florin Onișor-Gligor (Medicina, 2019)
Naso-orbito-ethmoid (NOE) fractures associated with anterior and posterior frontal sinus wall fractures are among the most challenging cranio-maxillofacial injuries. These represent a major emergency, having a potentially severe clinical picture, with intracranial hemorrhage, cerebrospinal fluid (CSF) leak, meningeal lesions, pneumocephalus, contusion or laceration of the brain matter, coma, and in some cases death. In this article, we present the case of a 30-year-old patient with the diagnosis of NOE fracture associated with bilateral anterior and posterior frontal sinus wall fractures caused by a horse kick, with a fulminant post-traumatic alteration of the neurological status and major impairment of the midface bone architecture. Despite the severity and complexity of the case, early initiation of correct treatment both in terms of intensive care and cranio-maxillofacial surgery led to the successful rehabilitation of the neurological status, as well as to the reconstruction and redimensioning of midface architecture and, not least, to the restoration of the patient’s physiognomy.